Stakeholder capability criteria of green procurement for construction projects in malaysia: a systematic review/ Afiqah Iliyana Samsul Bahari, Asmah Alia Mohamad Bohari and Natasha Khalil - Samsul Bahari, Afiqah Iliyana; Mohamad Bohari, Asmah Alia; Khalil, Natasha (Universiti Teknologi MARA, Perak, 2023)
Sustainable development goals (SDGs) affect many aspects of society, including the construction sector. The construction sector consumes about 40 to 75 percent of the total value of materials extracted globally and almost half of the electricity generated in the country. Therefore, the world needs to shift towards green environmental practices. The government has introduced green procurement as one of the green initiatives to save the environment. In Malaysia, green procurement is still in the introductory phase. Thus, the main challenges in green procurement implementation are the need for more knowledge among the stakeholders and the reluctance to accept the changes. The perceptions of various stakeholders regarding their environmental responsibilities depend on their capabilities and sense of responsibility. Therefore, this paper aims to identify the people's capabilities that would help boost the implementation of green procurement in the Malaysian construction industry. This paper highlights the outcome of the literature review using a systematic approach and a snowball approach. The articles were extracted from reputable databases such as ScienceDirect, Web of Science, and Scopus. Twenty-seven capabilities factors were identified from the systematic literature review, which will be further investigated in the next phase of the research. This research would contribute to the stakeholders in enhancing their capability to adopt green procurement. The right capabilities help an organisation obtain an opportunity and achieve outstanding performance.